Changes in Serum Adiponectin and Serum Leptin Levels Can Predict Pre-Eclampsia in Pregnant Women: A Prospective Study - Zia Ullah, Farukh Bashir, Kalsum Fatima, Shoaib Ahmed, Bakhtiar Hassan Tahir, Faiza Irshad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The study aims to investigate maternal adiponectin and leptin levels as prospective markers of preeclampsia, as well as the ratio of maternal adiponectin to leptin levels. Additionally, this research investigated the relationship between these two hormones. In addition to that, the purpose of this study was to analyze the connection that exists between the two hormones. Materials and Methods: This is a study that looks forward into the foreseeable future. The pregnant women who were willing to take part in the research were split into two groups: the first group, which was referred to as the study group, consisted of fifty women who had been diagnosed with pre-eclampsia, and the second group, which was referred to as the control group, consisted of fifty normotensive women of the same gestational age who did not have proteinuria. The levels of adiponectin, leptin, and their ratio were evaluated in the maternal serum of pre-eclamptic (the study group)and normotensive women(the control group).. The comparison's outcomes were analysed Results: There was a statistically significant difference in the levels of adiponectin found in the study group compared to the levels found in the control group. When comparing the levels of leptin in the study group with the control group, there was a statistically significant difference (p< 0.001) between the two groups. When compared to the control group, the ratio of adiponectin to leptin was considerably lower in the group that participated in the study (p<<0.001). When used as predictors of pre-eclampsia, serum leptin and the serum adiponectin/leptin ratio displayed a sensitivity of 90%, a specificity of 87.9%, a positive predictive value of 88.7%, and a negative predictive value of 73%. Additionally, the ratio of serum adiponectin to leptin exhibited a positive predictive value of 86.9 percent. Both the adiponectin/leptin ratio cutoff point and the leptin cutoff point were found to be optimal at 0.161. It was determined that a cutoff criterion of 24.1 ng/ml for serum leptin should be used. Both the adiponectin/leptin ratio and the serum leptin levels were significantly linked with significant degrees of accuracy (p <0.001) in the prediction of obesity. Conclusion: In research on pre-eclampsia, the examination of the maternal leptin level should be included, and a cut-off level of greater than 24.2 ng/ml should be employed as a diagnostic biomarker. This is due to the fact that pre-eclampsia is linked to hyperleptinemia, which is a condition that is characterised by dangerously high blood pressure in the mother. The ratio of adiponectin to leptin should be checked in every instance of preeclampsia, and the diagnostic threshold should be set to less than 0.153. This ratio is a potential biomarker for preeclampsia and should be examined in every case. Keywords: Leptin, adiponectin, the ratio of adiponectin to leptin, pre-eclampsia, and biomarkers